2002
DOI: 10.1080/09585190110092794
|View full text |Cite
|
Sign up to set email alerts
|

The antecedents of performance management among Finnish expatriates

Abstract: The present study aims at increasing the understanding of existing expatriate performance management practices, their ef ciency and related contextual factors. The descriptive ndings mainly support the picture arising from the few earlier studies identi ed, but also bring out several new ideas such as the use of team goals. Second, key performance management practices in uencing the perceived ef ciency of the system were identi ed, the key nding being that expatriate performance management with of cially set p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 17 publications
4
50
0
Order By: Relevance
“…Research points out advantages, such as the limitation of rater bias (Torno, 1993) or employee preferences to be appraised from multiple-perspectives (Bernardin, 1986), as well as disadvantages, such as the lack of economic justification (Scott & Einstein, 2001). In practice, however, the most common solutions are still based solely on employee supervisor appraisal, known as immediate manager appraisal (Suutari & Tahvanainen, 2002). Simultaneously, selfappraisal can also take place (Armstrong & Baron, 1998).…”
Section: B Buchelt 1968mentioning
confidence: 97%
See 1 more Smart Citation
“…Research points out advantages, such as the limitation of rater bias (Torno, 1993) or employee preferences to be appraised from multiple-perspectives (Bernardin, 1986), as well as disadvantages, such as the lack of economic justification (Scott & Einstein, 2001). In practice, however, the most common solutions are still based solely on employee supervisor appraisal, known as immediate manager appraisal (Suutari & Tahvanainen, 2002). Simultaneously, selfappraisal can also take place (Armstrong & Baron, 1998).…”
Section: B Buchelt 1968mentioning
confidence: 97%
“…Effective PM is extremely useful for MNCs, due to the fact that it can support such organizations in managing a unique and strategic group of employees, such as expatriates. This group is extremely important, due to their on the job responsibilities, including the opening of new strategic business units in foreign countries, developing business on an international scale and the transfer of knowledge necessary for the further development of the company (Suutari & Tahvanainen, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tahvanainen (2000) did not report a difference in the ways that key PM practices should be conducted in relation to the culture of the manager and subordinate; however, she used role-type variables as opposed to cultural variables. Suurati and Tahvanainen (2002) argued that expatriate PM should include clear goal-setting and evaluation mechanisms, but again cultural dimensions are not addressed. Sergeant and Frenkel (1998) did consider PM in relation to cultural differences, and along with Tung (1987), highlighted the importance of cultural training.…”
Section: Expatriate Performance Managementmentioning
confidence: 99%
“…While the performance of teams should also be evaluated, the focus of the performance appraisal in most fi rms remains on the individual employees (Mondy, Noe, & Premeaus, 2002). Performance appraisal is considered to be one of two key elements of performance management (Suutari & Tahvanainen, 2002). Greenberg (1986) suggested that procedural justice and distributed justice are the major factors that aff ect perceived fairness of performance appraisal.…”
Section: Fairness Perception Of Performance Appraisalmentioning
confidence: 99%